Determinan Leverage Pada Perusahaan Perbankan (Studi Pada Perusahaan Perbankan Terdaftar Di BEI 2016-2020) - Alfajri, Aldi (Jurnal Etnik: Ekonomi-Teknik, 2022)
Some of the research gaps above indicate that there are still inconsistencies between the variables studied in the previous study, their effect on the company's leverage. In addition, what distinguishes this research from previous studies using manufacturing companies is the selection of banking companies as objects. To determine the effect of tangible assets on Leverage. To determine the effect of firm size on Leverage. To determine the effect of profitability proxied by ROA on Leverage. To determine the effect of company growth on Leverage. This type of research is quantitative where the data processing uses statistical software in the form of SPSS version 25. This type of research also departs from statistically processed data and its presentation is carried out by referring to the principle of statistical data. The results of the study found that Tangible assets had no effect on Leverage in banking companies on the Indonesia Stock Exchange. The results of the study found that firm size had a positive and significant effect on Leverage. The test results found that Return on Assets supports the research hypothesis which expects a negative and significant effect on leverage, and the results show that ROA has a negative and significant effect on Leverage. The results of the study found that growth had no significant effect on leverage in banking companies on the Indonesia Stock Exchange. Profitability is proven to have a significant negative effect on leverage in banking companies on the Indonesia Stock Exchange, this means that the higher the company's profitability will reduce the company's leverage originating from debt.